Pronounced capping effect of olaminosomes as nanostructured platforms in ocular candidiasis management - Sadek Ahmed; Maha M. Amin; Sarah Mohamed El-Korany; Sinar Sayed (Taylor & Francis Group, 2022)
The aim of this study was to formulate and boost ocular targeting of Fenticonazole Nitrate (FTN)-loaded olaminosomes in order to improve drug corneal permeation and candidiasis treatment. Olaminosomes were formulated by ethanol injection technique applying a central composite design. The independent variables were: span 80 amount (mg) (A), oleylamine concentration (mg%) (B) and oleic acid: drug ratio (C). The dependent responses were: percent entrapment efficiency (EE %), particle size (PS), poly-dispersity index (PDI), zeta potential (ZP) and in vitro drug release after 10 hours (Q10h). Numerical optimization by Design-Expert® software was adopted to select the optimum formula. This formula was chosen based on highest EE %, ZP (as absolute value) and Q10h and lowest PS and PDI. The optimum formula was subjected to further in vitro characterization via Differential scanning calorimetry, Transmission electron microscopy, Fourier transform infrared spectroscopy, pH determination, effect of storage, influence of terminal sterilization, detection of Minimal Inhibitory Concentration and ex vivo corneal penetration analysis. Safety and antifungal activity of the optimum formula were tested through various in vivo studies like ocular irritancy, corneal tolerance, corneal uptake and susceptibility test. The optimum formula with the maximum desirability value (0.972) revealed EE% (84.24%), PS (117.55 nm), ZP (−74.85 mV) and Q10h (91.26%) respectively. The optimum formula demonstrated ocular tolerance with enhanced corneal penetration behavior (428.66 µg/cm2) and boosted antifungal activity (56.13%) compared to FTN suspension (174.66 µg/cm2 and 30.83%). The previous results ensured the ability of olaminosomes to enhance the corneal penetration and antifungal efficacy of Fenticonazole Nitrate.